Distribution of minor and trace metals in Carezza Lake (Antarctica) ecosystem - ACETO, Maurizio; SARZANINI, Corrado; ABOLLINO, Ornella; MENTASTI, Edoardo; G. Sacchero (1994)
This paper reports the distribution of a series of metals in natural samples collected at Carezza Lake in Antarctica, during the Italian Expedition in the austral summer 1989/90. The considered elements are: water, sediments and soil sampled from the surroundings of the lake and algae. The determination of the total concentration of the following metals was performed: Al, As, Ca, Cd, Co, Cr, Cu, Fe, Mg, Mn, Na, Ni, Pb, Zn. In addition, for sediment and soil samples, a speciation study was performed for some metals, namely Cd, Co, Cr, Cu, Fe, Mn, Ni, Zn, using the Tessier procedure.